Implementation of CoAP-Lite Protocol over USN - Jeong, Sun-Chul; Yu, So-Ra; Jung, Hoe-Kyung (Journal of Information and Communication Convergence Engineering, 9(5), 2011)
It is necessary for developing specific application protocol for mobile sensor end nodes and data collection devices that have constrained resources and computing powers. Because of these needs, IETF WG developed CoAP protocol and Internet draft was released, and processing to international standardization of this protocol. Because sensor nodes and information collection devices have restricted resources and computing powers, there are some limitations for applying to this proposed protocol directly. Thus in this paper we shows the implementation of full CoAP protocol for server, works on Linux and CoAP-Lite over telos which works on TinyOS for information collection devices. In this implementation we verified the main activities of CoAP protocol over USN by modifying some hardware with dependent algorithm. KCI Citation Count: 0